(untitled) (Afaq Lughawiyyah, 2024)
Al-Baroudi’s poems are often interspersed with different values. One of the values in which Al-Baroudi excelled in instigating and urging them is the value of consultation and justice, which he sometimes alludes to and highlights at other times, in his congratulations to Khedive Ismail, for the issuance of Islamic values by Al-Baroudi for a purpose other than his specific purpose - as we know -; It makes it difficult for the researcher to induct and extract for all its various purposes, as the matter requires knowledge of the linguistic sciences in all its arts, and knowledge of Islamic culture. The aim of the research is to show the extent of his skill in employing the faculty of language, wisdom, statement, and Islamic knowledge without affecting its poetic value and artistic construction. The research followed the descriptive and analytical method in his poetry, and the researcher reached impressive results and revealed to the researcher the intellectual backgrounds and the various techniques, such as the individualistic transition in which he lives to being preoccupied with the concerns of the people and serving the nation, in addition to the diversity in artistic images, and the Islamic values derived from the Holy Qur’an spread among the folds of The poem by Mahmoud Sami Al-Baroudi. This study is our contribution to the field of extracting values and studying the techniques and music of Al-Baroudi’s poetry.